DAMPAK DIGITALISASI TERHADAP PENINGKATAN KUALITAS PELAYANAN PUBLIK DI DESA SIPODECENG - Muliana Nursaleh; Herman Dema; Abdul Jabbar; Muhammad Rais Rahmat Razak; Mutiah Khaerunnisa (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study analyzes the impact of digitalization on public service quality in Sipodeceng Village, Baranti District, Sidenreng Rappang Regency using a SERVQUAL-based quantitative approach. Data were collected through surveys of 64 digital village service users and analyzed using simple linear regression with SPSS. Results show digitalization has a positive and significant effect on service quality (p=0.003, B=0.555, R²=0.135), improving speed, accuracy, accessibility, and transparency of services. Despite contributing 13.5%, findings demonstrate digitalization effectiveness at village level, though continued support remains necessary for communities with low digital literacy. The novelty lies in applying quantitative SERVQUAL analysis in rural South Sulawesi, integrating user perspectives in evaluating village digitalization, serving as reference for developing more adaptive and inclusive digitalization policies.